Bibliometry in the nanotechnology field: a comparative analysis of achievements in Russia and other countries - A. I. Terekhov (Библиосфера)
The article presents a comparative analysis of scientific performance of Russia in the field of nanotechnology. An initial corpus of publications was extracted from the Science Citation Index Expanded database through relevant keywords. It analyzes publications number, their citation, international co-authorship and its influence on citation for Russia and some countries among the most active in the field. Some intermediate results of implementing the Russian nanotechnology program are discussed.